Problematic smartphone use is associated with de Quervain's tenosynovitis symptomatology among young adults - Benites-Zapata, Vicente Aleixandre; Jiménez-Torres, Vanesa Esmeralda; Ayala-Roldán, María Pía (Musculoskeletal science & practice, 2021)
Previous research has reported an association between texting messages sent and De Quervain's tenosynovitis (DQT) symptomatology. However, these studies do not report smartphone dependence and DQT symptomatology. We aimed to evaluate the association between problematic smartphone use (PSU) and DQT symptomatology among young adults. Analytical cross-sectional study. We included adults between 18 and 25 years and evaluated DQT symptomatology's presence using the Finkelstein test. We used Experiences Related to Mobile Phone Use Questionnaire to measure the PSU. We carried out a generalized linear model from the Poisson family. We calculated the crude and adjusted prevalence ratios (PR) with their 95% confidence interval (CI). In total, we analyzed 491 subjects, the majority were women (52%), and the median age was 20 years. Of the total study population, 53% had positive results in the Finkelstein test, while 53% of the population had PSU. After adjusting our generalized linear model for confounders variables, we found that there is a higher prevalence of DQT symptomatology in those participants with occasional PSU and frequent PSU compared with participants without PSU, (aPR = 1.73, 95% CI: 1.47–2.05) and (aPR = 1.61; 95% CI: 1.29–2.00); respectively. We also found a higher prevalence of DQT symptomatology related to the number of hours per day in smartphones, pain with smartphones in the last week and using WhatsApp. We found a higher prevalence of De Quervain's tenosynovitis symptomatology in the people with problematic smartphone use. •Previous reports showed an association between texting messages and De Quervain's tenosynovitis.•Few studies reported smartphone dependence and De Quervain's tenosynovitis symptomatology.•We found an association between smartphone dependence and symptoms of De Quervain's disease.•The smartphone dependence study should accompany the diagnosis of De Quervain's tenosynovitis.